2010
DOI: 10.1007/s00330-010-1829-0
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolisation versus hysterectomy for leiomyomas: primary and 2-year follow-up results of a randomised prospective clinical trial

Abstract: UAE gave relief of symptoms (apart from menorrhagia) comparable to hysterectomy with less severe complications, but with an increased rate of secondary interventions. UAE may be the preferable treatment especially for patients with pressure symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…UAE is a radiological intervention that treats the entire uterine artery while preserving the uterus and it is now increasingly used as a safe and eVective treatment for symptomatic uterine Wbroids and an alternative to major surgery because this minimally invasive treatment can contribute to improved symptoms with few major complications. However, the eYcacy and safety of UAE for the treatment of symptomatic uterine Wbroids remain uncertain [5][6][7][8][9]. Thus, there has been a need for a careful assessment of the eYcacy and safety of UAE for symptomatic uterine Wbroids, particularly in comparison with standard surgical approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UAE is a radiological intervention that treats the entire uterine artery while preserving the uterus and it is now increasingly used as a safe and eVective treatment for symptomatic uterine Wbroids and an alternative to major surgery because this minimally invasive treatment can contribute to improved symptoms with few major complications. However, the eYcacy and safety of UAE for the treatment of symptomatic uterine Wbroids remain uncertain [5][6][7][8][9]. Thus, there has been a need for a careful assessment of the eYcacy and safety of UAE for symptomatic uterine Wbroids, particularly in comparison with standard surgical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there has been a need for a careful assessment of the eYcacy and safety of UAE for symptomatic uterine Wbroids, particularly in comparison with standard surgical approaches. Though many clinical randomized controlled trials (RCT) have evaluated the safety and beneWts of UAE for symptomatic uterine Wbroids, there is obvious inconsistency of eVects across those studies [5][6][7][8][9]. Thus, we Wrst designed a randomized trial comparing UAE and surgery to assess the eYcacy and safety, and then carried out a systematic review and meta-analysis to obtain an estimate of the eYcacy and safety of UAE for symptomatic uterine Wbroids based on the totality of published randomized evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, ultrasonography examination can provide sufficient detail to determine a patient's suitability for embolization and to identify relative contraindications such as pregnancy, uterine anomalies, endometriosis, adenomyosis, pelvic malignancy, and pedunculated fibroids. MRI is currently considered to be the most accurate imaging technique for detection and localization of fibroids (Ruuskanen et al, 2010). MRI is more sensitive than ultrasonography in the detection of fibroids.…”
Section: Preprocedures Testingmentioning
confidence: 99%
“…MRI may also accurately assess an enlarged fibroid uterus, which is not possible with ultrasound because of the limited field of view. The capability of MRI to demonstrate the uterine zonal anatomy allows accurate classification of individual masses as submucosal, intramural, or subserosal (Ruuskanen et al, 2010). Contrast materialenhanced MR imaging exceeds ultrasound's technical limitations in precise fibroid mapping and characterization.…”
Section: Preprocedures Testingmentioning
confidence: 99%
“…Following the blockage, blood flow is reduced, and ischemia and necrosis will occur in fibroma which has larger diameter vessels [4]. Several studies have reported effectiveness of UAE in reducing menorrhagia and pelvic pain caused by fibroma [5][6][7][8][9]. UAE reduces fibroma size and its complications [10,11].…”
Section: Introductionmentioning
confidence: 99%